THE EFFECT OF DIE/BLANK HOLDER ANGLES ON LIMIT DRAWING RATIO AND WALL THICKNESS IN DEEP DRAWING OF SQUARE CUPS - Ozek, Cebeli; Unal, Engin (Gazi Univ, Fac Engineering Architecture, 2012)
This study presents an attempt to determine the effect of various angles of die/blank holder, radiuses of die/punch and die/blank holder force on drawing ratio and the wall thickness to form square cups in angular deep drawing dies using DIN EN10130-1999 sheet material. For this purpose, the die/blank holder profile with angles of alpha=0 degrees, alpha=5 degrees, alpha=10 degrees, alpha=15 degrees and die/punch profile with radiuses for R=4, R=6, R=8, mm. The punch has diameter of 50 mm and the die has a diameter of 47.6 mm, which gives 1.20 mm of clearance. Shell Tellus 68 oil was used between the die and the blank to reduce frictional resistance. The beta value was enhanced from 1.86 (alpha=0) to 2.32 (alpha=15 degrees) additionally, the Wall thickness values were measured as 0.637, 0.664, 0.733 and 0.742 mm for 0 degrees, 5 degrees, 10 degrees and 15 degrees angle a values, respectively. As a consequence, it was observed that the new type's angular deep drawing dies gave better results with different angle and radiuses values than conventional dies with higher drawing ratio.
Keywords: Square cups; angular deep drawing; limit drawing ratio